2017
DOI: 10.14202/vetworld.2017.61-66
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of gastrointestinal parasitism in small ruminants in western zone of Punjab, India

Abstract: Aim:The aim of this study was to explore the prevalence of gastrointestinal parasitism in small ruminants in relation to various risk factors in the western zone of Punjab.Materials and Methods:During the study, 603 fecal samples (391 of sheep and 212 of goats) were examined qualitatively by floatation and sedimentation techniques, and quantitatively by McMaster technique.Results:Out of the 603 fecal (391 sheep and 212 goats) samples examined, 501 were found positive for endoparasitic infection with an overall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

19
35
4
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(60 citation statements)
references
References 7 publications
19
35
4
2
Order By: Relevance
“…On the other hand, young animals are less affected by parasitic infections due to consumption of less amount of vegetation and less exposure for grazing as they mainly depend upon milk feeding. Our findings were in concordance with Singh et al (2017); Yadav et al (2006); and Emiru et al, (2013) who recorded a higher prevalence of infection in adults than young ones. Gupta et al (2013) and Sutar and Khan (2011).…”
Section: Resultssupporting
confidence: 94%
“…On the other hand, young animals are less affected by parasitic infections due to consumption of less amount of vegetation and less exposure for grazing as they mainly depend upon milk feeding. Our findings were in concordance with Singh et al (2017); Yadav et al (2006); and Emiru et al, (2013) who recorded a higher prevalence of infection in adults than young ones. Gupta et al (2013) and Sutar and Khan (2011).…”
Section: Resultssupporting
confidence: 94%
“…This phenomenon of high nematode prevalence is not new in tropical countries. Similarly high levels of nematode infection like 83.08%, 88.9%, and even 100% have been reported in India, Rwanda, and Pakistan, respectively [ 3 , 22 , 28 ]. In the present study, sheep and goats were raised under an extensive management system, in mostly low-lying pastures where stocking densities were high, nutrition was limited, and veterinary care was almost nonexistent.…”
Section: Discussionmentioning
confidence: 76%
“…Overall prevalence of H. contortus infection in small ruminants has been reported variably by different studies from as low as 52.7 to over 83% [ 13 , 15 , 16 , 21 , 22 ]. One Ethiopian study reported a prevalence of 67.2% and 56.6% in sheep and goats, respectively [ 16 ], indicating greater susceptibility of sheep.…”
Section: Introductionmentioning
confidence: 99%
“…It was documented that the effects of ectoparasite infestations are more pronounced in heavy and mixed infestations [30][31][32]. Thus, this high dual infestation of M. ovinus and B. ovis in sheep in this study suggests that the effects of infestations were so pronounced on the animals.…”
Section: Discussionmentioning
confidence: 47%